Consumer Protection in Digital Environment in Pakistan - Yasir Arfat,; Naveed Hussain,; Usama Mukhtar, (Dialogue Social Science Review (DSSR), 2024)
Development of technology and specifically information technology has changed the way things were done and dealt in past. Buying and purchasing feature of humans is as old as making being basic need and necessity. Various measures had also been taken to protect the interest of parties. In a contract of sale, the seller focusses on consideration which is mostly certain like a specific currency and quantum of that very currency but the purchaser is uncertain about many things like quality, durability, originality and certainty. Law of consumer protection deals with the buyers of commodities and services to ensure that they are not exploited by the sellers and service providers. With the evolution of information technology and digitalization these contracts are taking place online and to ensure the protection of consumer rights has become more complex especially in transnational commercial activities. The present research study has highlighted that what are the possible issues that may arise with a focus on protection of consumer rights. In online transactions and week jurisdictions like Pakistan it is double edged sword that on one end customer do not find appropriate remedies and on the other end consumer activism brings a bad name for those enterprises who are really concerned about their name and repute. Tips have been provided that how good businesses can avoid unnecessary litigation and bad repute. It has also been suggested that consumer courts must realize the importance of online consumers because that is need of time and that saves a lot of energy, resources and cost. During the era of Covid 19 it importance was multiplied so these online consumers deserve same level of protection like on the counter consumers.